Analisis Pola Pertumbuhan dan Morfometrik Udang Jerbung (Penaeus merguiensis De Man, 1888) di Perairan Sekitar Bakoi, Sorong Selatan - Ridwan Sala; Roni Bawole; Aldrin Bonggoibo; Thomas Frans Pattiasina; Sampari Suruan; Ferawati Runtuboi (Faculty of Agriculture Musamus University, 2021)
The waters of South Sorong have potential shrimp resources, including abundant banana shrimp (Penaeus merguiensis de Man, 1888). This study aims to obtain information about the morphometric characteristics and growth of banana shrimp in the fishing area around the waters of Kampung Bakoi, South Sorong Regency, West Papua Province. Data collections were carried out in June and October 2019 using descriptive methods with direct observation techniques. Based on the results of data analysis, it was found that the total length of shrimp caught in Bakoi Village was in the range of 10 - 26.8 cm and the most were caught measuring 15.2 cm to 16.4 cm. The model of the relationship between length and weight of banana shrimp in Bakoi Village follows the equation Log W= 1,630+2,659 Log (L) or the form of negative allometric growth. Analysis of the relationship between total length (Y) and carapace length (X) (including rostrum) and the relationship between total length and carapace length (Z) (excluding rostrum) obtained the best estimator models, each following the logarithmic equations L = -2,188 + 10,226 Ln(PK) and L = 4,439 + 9,201 Ln(PKt) respectively.